Pelatihan Budidaya Sayuran dengan Sistem Hidroponik Sebagai Usaha Pemberdayaan Wanita Desa Undaan Lor - Zulfikasari, Sony; Anggono, Wisnu Aji Suryo; Hamham, Haniu; Fauzi, Azka Patria; Supriyadi Supriyadi (Jurnal Bina Desa, 2025)
The community service of UNNES GIAT 9 students aims to introduce and train the making of hydroponic plants to PKK mothers in Undaan Lor Village, Karanganyar District, Demak Regency. In this village there is no application of the hydroponic method, while this method has the potential to improve food security and farming efficiency on limited land. The method used was community service and training in the form of socialization and hands-on training. The socialization was held on July 9, 2024 at Undaan Lor Village Hall, covering the basic introduction of hydroponics, its benefits, and applications. Practical training was conducted on July 20, 2024 at the post, including seeding and planting vegetable plants hydroponically. The results of the activity showed high enthusiasm from the participants, increased understanding of hydroponics, and the ability of the participants to practice the method. The evaluation showed the success of the program, with participants being able to make hydroponic plants according to the material taught and intending to apply it in their respective homes. This activity succeeded in introducing an efficient and environmentally friendly alternative farming method to the people of Undaan Lor Village.